S57 Serine proteases in house dust mite extract mediate PAR-2-associated calcium signaling and a pro-inflammatory response in asthma human primary bronchial epithelial cells. (11th November 2022) - Ouyang, X; Reihill, JA; Douglas, LEJ; Martin, SL
Abstract : Introduction and Objectives: Exposure to house dust mites (HDM) is commonly linked with the development and progression of allergic asthma. HDM contain trypsin-like (TLPs) and chymotrypsin-like serine proteases and cysteine proteases which can compete with endogenous enzymes to cleave the extracellular amino terminus of protease-activated receptors (PARs). The newly exposed amino terminal 'tethered ligand' activates the receptor, triggering calcium signalling and a concomitant increase in pro-inflammatory cytokine expression. The objective of this study was to dissect the protease components of HDM extract to assess their activation of PARs and effect on inflammatory mediators, IL-33 and TSLP. Methods: HDM was pre-treated with E-64 and a novel bioactive peptide, PE-BBI (Reihill et al, Biomolecules 2020; 10(4):515) or aprotinin to selectively inhibit cysteine and serine proteases, respectively or was heat-inactivated (HI-HDM) to abolish all protease activity before being added to human primary asthmatic bronchial epithelial cells (hPBECs) in submerged cultures for 2 and 48 hrs. Calcium mobilization was determined by quantification of the fluorescent signal using the Fluo-4 Direct™ Calcium Assay Kit and FlexStation (Molecular Devices). IL-33, TSLP mRNA expression was measured by TaqMan gene expression two step RT-qPCR. Results: No difference was observed in calcium mobilization between HDM and HDM pre-treated with E-64. In contrast, calcium mobilization was reduced by 73% and 76%, when HDM was pre-treated with PE-BBI and aprotinin, respectively. Prior treatment of hPBECs by HDM had little impact on the PAR2 agonist peptide, 2-FLI's ability to induce calcium mobilization. In contrast HDM prevented a further trypsin-induced increase of intracellular calcium levels. Pre-treatment of HDM with PE-BBI however, selectively abolished the impact of HDM on trypsin-induced calcium mobilization, whereas aprotinin prevented both HDM and trypsin from inducing calcium mobilization. An increase in IL-33 or TSLP mRNA expression in the presence of HDM was not observed upon treatment with HI-HDM and was reduced when HDM was pre-treated with aprotinin. Conclusion: Our data showed that HDM serine proteases can induce PAR-2 associated calcium signaling and increased IL-33 and TSLP expression in asthmatic airway cells. These observations contribute to our understanding of HDM-induced inflammation and possibly epithelial barrier dysfunction in asthmatic airways.